PROFIN THẲNG ĐỨNG CỦA TỐC ĐỘ GIÓ TRONG LỚP KHÍ QUYỂN SÁT ĐẤT VÀO THỜI KỲ CHUYỂN TIẾP, TẠI PHƯỚC HÒA, BÌNH ĐỊNH VÀ ỨNG DỤNG - Lưu, Lê Văn; Huy, Lê Việt; Thành, Phạm Xuân; Sơn, Hoàng Hải (Vietnam Journal of Earth Sciences, 2017)
Based on continuous measurement data during transitional period of 1999 and 2000 at four levels 10, 20, 30 and 40 m at Phuoc Hoa, Binh Dinh, the authors have established wind speed vertical profile.Results show : wind speed vertical profile follows the logarithmic law, with Z0 = 0.019 m. If we use tenelectric generators by wind energy NORDEX-52(1000 kW), we will have 1,317,600 kWh during transitional period at this position.